Dynamics of Environmental Issues in Indonesia: Critical Discourse Analysis of the #perubahaniklim Digital Campaign Through TikTok - Khairul Syafuddin (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
Environmental issues in Indonesia have become a widely discussed topic. This is driven by many emerging environmental problems, such as water quality, deforestation, air pollution, and waste management. These various problems have encouraged environmental activists to speak up on TikTok to convey their aspirations. This effort is part of society's role in achieving the goals of the SDGs program. This study aims to analyze the discourse built by influencers on TikTok in campaigning for environmental issues that focus on climate change. This study uses a descriptive qualitative approach with a critical paradigm. The method used in this study is the critical discourse analysis model of Teun A. van Dijk to explain how language functions in a social context and shapes people's thoughts and behavior, primarily through the TikTok algorithm. The results of this study indicate that the discourse produced by influencers considers the use of language to build closeness with the audience. In addition, there are efforts to position the audience as the subject so that it can encourage their empathy for climate change. In addition, the rhetoric and narratives produced are made by considering environmental algorithms to provide implications for the audience.